Structural, electronic, magnetic, optical and optoelectronic properties of the sprayed cobalt doped ZnO nanostructured thin films. (13th July 2018) - El Haimeur, A; Zarhri, Z; Bouaouda, M; Colin, J; Addou, M; ElKenz, A
Abstract: In this paper, we theoretically and experimentally investigated the structural, electronic, optical and magnetic properties of Cobalt doped ZnO. We used the the SPRAY Pyrolysis technique on preheated substrate glass. Samples were characterized using x-ray Diffraction. Optical parameters such as the optical band gap energy (Eg), the refractive index (n), the dielectric constants ( ϵ r, ϵ i) and the optical conductivity ( σ ) as a function of photon energy have been investigated. As main result, 2% Co doping leads to improve the optical and optoelectronic properties of ZnO with a higher refractive index, optical conductivity and absorption near infrared region. Furthermore, we investigated the doping concentration effect on the magnetic and structural properties by first principal calculations and found a promising phase change temperature which is higher than room temperature.